Growth performance and intestinal histomorphology of Nile tilapia juveniles fed probiotics - Nakandakare, Ivan Bernardoni; Iwashita, Marina Keiko Pieroni [UNESP]; Dias, Danielle De Carla [UNESP]; Tachibana, Leonardo; Ranzani-paiva, Maria José Tavares; Romagosa, Elizabeth (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
The objective of this study was to assess the growth performance and the histomorphometric characterization of the middle intestine of GIFT strain Nile tilapia, Oreochromis niloticus juveniles fed probiotics, added either before or after the feed processing. The experimental design was completely randomized, with five treatments and five replications: pelleted feed without any probiotic; pelleted feed with inclusion of probiotic before the processing; pelleted feed with inclusion of probiotic after the processing; extruded feed without any probiotic and extruded feed with inclusion of probiotic after the processing. Two hundred and fifty juveniles were distributed in 25 aquaria (20L) and fed for 63 days. Differences in the mean values of total weight were found at the end of the experiment. After 42 days of feed intake, significant differences in feed conversion were verified for treatments with extruded diets when compared to the pelleted ones. The fishes fed diets supplemented with probiotic presented increase in the thickness of the epithelium of the intestine. The best zootechnical performance was observed in the extruded diet supplemented with probiotic added after the feed processing. The inclusion of 4.0 x 10(8) CFU g-1 of Bacillus subtilis and 4.0 x 10(8) CFU g-1 of Bacillus toyoi in both the pelleted and the extruded diets promoted an increase in the thickness of the epithelial layer of the middle intestine.

Objetivou-se avaliar o desempenho zootécnico e a caracterização histomorfométrica do intestino médio de juvenis de tilápias do Nilo, Oreochromis niloticus, variedade GIFT, alimentadas com probiótico, incluído antes e após o processamento de ração. O delineamento experimental foi inteiramente casualizado com cinco tratamentos e cinco repetições composto pelos seguintes tratamentos: ração peletizada sem probiótico; ração peletizada com inclusão do probiótico antes e após o processamento; ração extrusada sem probiótico e ração extrusada com inclusão do probiótico após o processamento. Duzentos e cinqüenta juvenis foram distribuídos em 25 aquários (20L) e alimentados durante 63 dias. Foram constatadas diferenças para os valores médios do peso total no final do experimento. Após 42 dias de alimentação foram verificadas diferenças significativas na conversão alimentar para tratamentos com as dietas extrusadas comparadas com as peletizadas. Os peixes alimentados com as dietas suplementados com o probiótico apresentaram aumento na espessura da camada epitelial do intestino. O melhor desempenho zootécnico foi observado, na dieta extrusada suplementada de probiótico incorporado após o processamento de ração, e a inclusão de 4.0 x 10(8) CFU g-1 of Bacillus subtilis e 4.0 x 10(8) CFU g-1 of Bacillus toyoi, em dietas peletizadas e extrusadas, promoveu o aumento na espessura da camada epitelial do intestino médio.
Desempenho produtivo e histomorfologia intestinal de juvenis de tilápia do Nilo alimentados com probióticos
Keywords: Bacillus; intestino; processamento de ração; suplemento; Bacillus; intestine; feed processing; supplement